RhIAr/AuIAr Transmetalation, a case of group exchange pivoting on formation of M-M bonds via oxidative insertion - Garcia Melchor, Max (My University, 2019)
By combining kinetic experiments, theoretical calculations, and microkinetic modeling, we show that Pf/Rf (C6F5/C6Cl2F3) exchange between [AuPf(AsPh3)] and trans‐[RhRf(CO)(AsPh3)2] does not occur by typical concerted Pf/Rf transmetalation via electron‐deficient double bridges. Instead, it involves asymmetric oxidative insertion of the RhI complex into the (Ph3As)Au−Pf bond to produce a [(Ph3As)Au−RhPfRf(CO)(AsPh3)2] intermediate, followed by isomerization and reductive elimination of [AuRf(AsPh3)]. Interesting differences were found between the LAu−Ar asymmetric oxidative insertion and the classical oxidative addition process of H2 to Vaska complexes.
PUBLISHED
Keywords: Rhodium; Gold; Oxidative Addition; Bimetallic catalysis; Density functional calculations